Clinical and Radiographic Assessment of Platelet-Rich Plasma (PRP) versus Traditional Blood Clot Scaffold in Revascularization of Immature Permanent Teeth: A Comparative Study - Kashif Adnan, Waqas Ahmad Farooqi, Azeem Hussain Soomro, Farhad Ishaq Amir, Asrar Ahmed, Syeda Kinza Asghar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Regenerative endodontic procedures (REPs) are applied in the treatment of necrotic immaturepermanent teeth more and more frequently, platelet-rich plasma (PRP) and classic blood clot (BC) are used as commonly